HYPERSPERMIA, THE OFTEN-NEGLECTED SEMEN ABNORMALITY AFFECTING FECUNDABILITY - Markus Christian Hartanto; Cennikon Pakpahan; Aleksander Try Utomo (Universitas Airlangga, Surabaya, Indonesia, 2024)
Highlights Hyperspermia is often ignored, but it can affect fecundability by diluting sperm and reducing sperm concentration. Hyperspermia might be associated with genetic causes and male accessory gland infections, but no specific treatment is mentioned to treat this condition. Abstract Background: Hyperspermia is defined as a seminal volume greater than 6.3 ml. This definition is often ignored by physicians, while it may affect fecundability. Objective: To report a case of an adult with hyperspermia that affects his fecundability and to discuss it with the scoping review's result. Case: A 30-year-old man came desiring to have a child. He had regular sexual intercourse with his wife for the last 3 months, after living in different cities before. Based on the semen analysis, it was found that he had hyperspermia (volume 8.2 ml) and oligozoospermia (sperm concentration 4.25 million/ml). After taking antioxidants, the seminal volume was lowered, and the couple got pregnant. Method: A scoping review was conducted by using guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews (PRISMA-ScR). After a comprehensive search based on the inclusion and exclusion criteria, only 3 original research were retrieved due to the rarity of articles regarding this topic. Discussion: According to previous studies, hyperspermia can affect fecund-ability by diluting the sperm, causing sperm concentration to be decreased as in this case. Genetic mutation and male accessory gland infection may be contributing factors to hyperspermia. No consensus and studies about the treatment are available. Conclusion: Hyperspermia is a semen parameter alteration that needs to be taken care of to increase fecundability.